The owl and the nightingale - Armitage, Simon, 1963- (Princeton University Press, 2022)
"One of the earliest literary works to be written in Middle English and one of the first comic poems in the English language, The Owl and the Nightingale (1189-1216) is an anonymous work that describes a debate between two birds. In arguing about such topics as love, marriage, and nesting habits, the owl and the nightingale address issues that remain relevant to contemporary society, such as identity, cultural background, class distinctions, and the right to be heard. The British Library describes it as "a humorous piece of avian mud-slinging as the birds quarrel, not always good-naturedly." It is composed of octosyllabic couplets in an early form of Middle English from before the age of Chaucer. Some scholars see it as a commentary on different traditions of debate; others read it as a reflection of modern scientific thinking on the differences between the human and the animal. The award-winning poet Simon Armitage has translated the 1,700-line poem using full rhyming couplets in iambic octameter. The book includes a facing-page translation of the poem, along with an introduction by Armitage. To produce the translation he worked from facsimile and transcribed editions of the two surviving manuscripts, one at the British Library and one at Jesus College, Oxford, as well as from several other published and online resources. Having already translated Sir Gawain and the Green Knight, The Death of King Arthur, and Pearl, he expects that this is his last medieval translation"-- Provided by publisher.
Keywords: Birds -- Poetry.; Debate poetry, English (Middle); Debate poetry, English (Middle) -- Translations into English.; Civilization.; Electronic books.; Oiseaux -- Poésie.; Civilisation.; Livres numériques.; civilization.; e-books.; POETRY / Medieval.; Birds; Adultery.; Age of the Earth.; Age of the universe.; Aircraft.; Alien Technology.; Alien visitation.; Alpha Centauri.; Apollo program.; Aptitude.; Aristotle.; Arthur C. Clarke.; Astrology.; Astronomer.; Astronomy.; Atomic number.; Author.; Authorship.; Baking.; Billion years.; Chemical element.; Complication (horology).; Cosmic microwave background.; Courtesy.; Crone.; Crop circle.; Designer.; Dirge (Transformers).; Disgust.; Dwarf planet.; Earth's orbit.; Earth.; Embarrassment.; Exoplanet.; Foe (novel).; Galileo Galilei.; General relativity.; Genre.; Geocentric model.; Gravity.; Harassment.; Horoscope.; Hour.; Hubble Space Telescope.; In Death.; Indiscretion (Star Trek Deep Space Nine).; Intention.; International Astronomical Union.; Interstellar medium.; Kepler's laws of planetary motion.; Lament.; Light-year.; Literature.; Martian.; Medieval poetry.; Mercury (planet).; Meteorite.; Microorganism.; Microsoft.; Military aircraft.; Misery (novel).; Misfortune (folk tale).; Monologue.; Moon rock.; Mount Wilson Observatory.; National Air and Space Museum.; Neptune.; Neutron.; Newton's laws of motion.; Orbit.; Pierre-Simon Laplace.; Pity.; Poetry.; Prediction.; Radiometric dating.; Residence.; Result.; Rodent.; Science.; Scientist.; Self-awareness.; Singing.; Skepticism.; Slinky.; Spacecraft.; Spiral galaxy.; Tactic (method).; Technology.; Tendril.